Generalised Semi Closed Sets in Grill Topological Spaces - Palaniappan, Y.; Raj, S. Vibin Salim; Kumaran, V. Senthil (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2021)
The purpose of this paper is to introduce and investigate a new class of generalized semi closed sets in terms of Grill G on X. The characterization of such sets along with certain other properties of them are obtained.